Generation of Gait Events with a FSR Based Cane Handle. - Trujillo-León, Andrés; De-Guzmán-Manzano, Arturo; Velázquez, Ramiro; Vidal-Verdú, Fernando (MDPI, 2021)
Gait analysis has many applications, and specifically can improve the control of prosthesis, exoskeletons, or Functional Electrical Stimulation systems. The use of canes is common to complement the assistance in these cases, and the synergy between upper and lower limbs can be exploited to obtain information about the gait. This is interesting especially in the case of unilateral assistance, for instance in the case of one side lower limb exoskeletons. If the cane is instrumented, it can hold sensors that otherwise should be attached to the body of the impaired user. This can ease the use of the assistive system in daily life as well as its acceptance. Moreover, Force Sensing Resistors (FSRs) are common in gait phase detection systems, and force sensors are also common in user intention detection. Therefore, a cane that incorporates FSRs on the handle can take advantage from the direct interface with the human and provide valuable information to implement real-time control. This is done in this paper, and the results confirm that many events are detected from variables derived from the readings of the FSRs that provide rich information about gait. However, a large inter-subject variability points to the need of tailored control systems.
Keywords: Biomecánica; Biosensores; Prótesis; Ingeniería biomédica; Gait; Gait events; Gait monitoring; FSR sensors; Instrumented cane; Assistive technology; Prosthesis; Exoskeletons